Decapod abundance and species richness in the bycatch of Xiphopenaeus kroyeri (Heller, 1862) fishery, Santa Catarina, southern Brazil - Stanski, Gilson [UNESP] (2019)
We aimed to analyze the crustacean bycatch from the Xiphopenaeus kroyeri fishery in the Santa Catarina State and compare the bycatch's biomass to that of the target species. Shrimp and environmental factors were sampled monthly from July 2010 through June 2011. For each crustacean species, we calculated the number of individuals, the relative abundance and the occurrence frequency. The relative abundance was classified as very abundant (Va), abundant (Ab) or low abundance (La), while the occurrence frequency was labeled continuous (Co), accessory (Ac) or accidental (Ad). We observed a total richness of 28 species, which is considered high for a subtropical region. Brachyura was the most frequent taxon (74%) followed by Penaeiodea (18%). Five species were considered Va (Arenaeus cribrarius, Callinectes danae, C. ornatus, Isochelis sawayai and Pleoticus muelleri), and eight species were considered Co (A. cribrarius, C. danae, C. ornatus, Farfantepenaeus paulensis, Hepatus pudibundus, Libinia spinosa, Litopenaeus schmitti and Sicyonia dorsalis), suggesting that the studied environment is heterogeneous and provides a variety of microhabitats, enabling many species to coexist. Therefore, the high species richness observed demonstrates the ecological importance of this region and thus the necessity of strategies aiming to minimize the impacts caused by trawling fisheries.